Are the blue daemons really blue? Multidisciplinary study for the colours characterization of the mural paintings inside the Blue Daemons Etruscan tomb. - Ceccarelli, Sofia; Guarneri, Massimiliano; Romani, Martina; Giacopini, Lucina; Francucci, Massimo; Ciaffi, Massimiliano; De Collibus, Mario Ferri; Puiu, Adriana; Verona-Rinati, Gianluca; Colao, Francesco; Fantoni, Roberta (Journal of Cultural Heritage, 2021)
• A multidisciplinary study for the colours characterisation of the Blue Daemons tomb is presented; • 3D colour model of the tomb achieved with the RGB-ITR laser scanner; • Check of the colours collected by the scanner using spectrophotometry technique • The identification of colours was carried out through spectroscopy techniques (Raman, XRF, LIF); • Multidisciplinary and multispectral approaches for studying the colorimetric contamination caused by the presence of consolidants • The integration of 3D modelling, colorimetric and spectroscopic methodologies enable the description of the tomb's state of health, both in term of pigments and structure. This paper presents the results of a multidisciplinary study carried out for the characterisation of the colours of a famous Etruscan site: the Blue Daemons tomb. Here, 3D digitalisation and analytical investigations were necessary for conservative and educational purposes, in order to characterize the materials of the Etruscan art, preserve the memory of the archaeological remain and be able to transmit it to future generations. The 3D model of the tomb has been achieved with the multi-wavelengths laser scanner prototype developed by ENEA, allowing a truthful colour and structural digitalisation of the tomb without the influence of the bad illuminating conditions. Such a technique introduced a doubt about the validity of the tomb name: the daemons are really blue? Colorimetric measurements achieved with both the laser scanner prototype and a portable spectrophotometer have revealed greyish hue of the demoniac figures, requiring further and focused analyses on the colour palette of the painting in order to understand their composition and the state of conservation. For these purposes, Raman, XRF and LIF spectroscopies have been performed on the wall where the blue demons are represented. The results have detected the use of the pigment Egyptian blue for the daemons' skin and ochres for yellow and red details, confirming the legitimacy of the tomb name, although the presence of synthetic consolidants applied in previous restorations have altered colorimetric measurements.